2006
DOI: 10.1017/s0265021506000974
|View full text |Cite
|
Sign up to set email alerts
|

Preventing pain during injection of propofol: effects of a new emulsion with lidocaine addition

Abstract: Premixing propofol medium-chain triglyceride/long-chain triglyceride with lidocaine is one of the most effective measures currently available to reduce the incidence of injection pain in sedated patients during regional anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
(28 reference statements)
1
11
0
Order By: Relevance
“…This is in agreement with a recently published study that used a lower dose of lidocaine [14]. Unfortunately, the addition of lidocaine to propofol involves extra work and introduces associated drug-mixing risks e.g.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with a recently published study that used a lower dose of lidocaine [14]. Unfortunately, the addition of lidocaine to propofol involves extra work and introduces associated drug-mixing risks e.g.…”
Section: Discussionsupporting
confidence: 92%
“…The appropriate sample size was estimated based on the assumption that we were interested in an incidence reduction of propofol-LCT/MCT injection pain by 15% with the premixed group having an incidence of 23% for propofol-LCT/MCT injection pain in a previous study [7,11]. This yielded a sample size of 105 subjects per group with α = 0.05, β = 0.8, using Fisher exact test with the G-power program.…”
Section: Methodsmentioning
confidence: 99%
“…Reports show that pretreatment with lidocaine with a tourniquet has a better effect than a premixed injection with propofol-LCT [2] but not consistently. Furthermore, propofol-LCT/MCT was introduced as a new chemical agent with less injection pain than propofol-LCT [7,8], and lidocaine is effective for reducing injection pain of this agent [9]. However, no comparative studies have been done on the preventive effect of injection pain between a premixed injection and pretreatment of lidocaine during propofol-LCT/MCT administration in the same clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Yamakage and colleagues reported that by using a mix of medium and long chain triglycerides, the aqueous propofol concentration was decreased by up to 40% compared to using only long chain triglycerides [8]. It has also be shown that using a medium/long chain triglyceride propofol emulsion reduced the injection pain incidence to 47% compared to 60% when using a long chain triglyceride propofol emulsion [9].…”
Section: Conflict Of Interestmentioning
confidence: 99%